PENGARUH KREDIBILITAS INFLUENCER TERHADAP SIKAP PADA MEREK - Sugiharto, Shiya Azi; Ramadhana, Maulana Rezi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2018)
One way to promote the brand and to increase awareness to the public is to use influencers, and one of the influencersused by Maybelline is Tasya Farasya. The purpose of this study was to determine the effect of influencer credibility onattitudes on the Maybelline brand. In addition, this study also aims to determine the credibility factors of influencersthat most influence attitudes on the Maybelline brand. This research uses descriptive correlational method using aquantitative approach. This study uses a simple linear regression method because there is one independent variable andone dependent variable. The population in this study were female students of the Telkom University Faculty ofCommunication and Business who had watched and or followed a video made by Tasya Farasya regarding Maybellineproducts. The number of samples used in this study were 100 respondents.In this study has a positive effect between the variable credibility of influencer (X) on the attitude variable on the brand(Y) on the Maybelline brand. This is evidenced by hypothesis testing using the - t test. The data produces that the valuet_count (7.334)> t_ (table) (1.984). The credibility factor of influencers that most influences attitudes towards brand isattractiveness.